Overview of sepsis associated acute kidney injury: literature review - Al-Shahrani, Mona; Soofy, Sarah Khalil; Mohammad, Mouaz Abdullah; Alfalahi, Ibrahim Yahya; Alhazmi, Ali Alhussain; Alabdali, Hammad Ahmed; Alahmadi, Raghad Abdulrahman; Alutaibi, Rakan Saqer; Alluhaidah, Abdullah Mohammed; Almalki, Khalid Seraj; Alamri, Fahad Zaid; Alhutaylah, Mahdi Ali (International Journal Of Community Medicine And Public Health, 2021)
The incidence of acute kidney injury has been estimated to be around a fifth of the adult patients during their hospital stays. Sepsis is estimated to be the commonest cause for AKI development in critically-ill patients; contributing to the pathology in 20-50% of the cases. We reviewed some aspects of sepsis-associated AKI. Among the risk factors that may contribute to the development of AKI, age, sex, and the presence of comorbidities as diabetes, heart, and liver diseases were reported as significant factors associated with the development of the condition. The pathophysiology of sepsis-induced AKI is still unclear; however, some authors said that it may be related to the hypoperfusion of the renal tissue and subsequently induced ischemia. This theory was supported by animal studies; however, other investigations on humans reported no association between the two events. On the other hand, we believe that sepsis-induced AKI is probably due to the associated severe inflammatory state and hemodynamic instability are the main accusants. The management of this condition requires early diagnosis and early intervention by managing sepsis. Moreover, vasopressors as epinephrines have proved efficient in managing the shock state, even better than renal replacement therapy.